The Effect of Interest Rates and Inflation on Loan Growth and Non Performing Loan (Literature Review of Financial Management) - Novarina Ayu Rahmananingtyas (Dinasti Publisher, 2022)
Literature Article Review of the Effect of Interest Rates and Inflation on Loan growth and Non-Performing Loans in Loan Companies is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in future research, within the scope of Financial Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) interest rates affect loan growth; 2) inflation affects loan growth; 3) interest rates affect Non-Performing Loans 4) inflation affects Non-Performing Loans and 5) Loan growth affects Non-Performing Loans Apart from these 2 exogen variables that affect endogenous variables p loan growth and Non-Performing Loans There are many other factors, including banking policy variables , economic growth and credit analysis.